Sialic acids regulate microvessel permeability, revealed by novel in vivo studies of endothelial glycocalyx structure and function - Betteridge, Kai; Arkill, Kenton; Neal, Chris; Harper, Steve; Foster, Becky; Satchell, Simon; Bates, David O.; Salmon, Andy (Wiley, 2017)
The endothelial glycocalyx forms a continuous coat over the luminal surface of all vessels, and regulates multiple vascular functions. The contribution of individual components of the endothelial glycocalyx to one critical vascular function, microvascular permeability, remains unclear. We developed novel, real time, paired methodologies to study the contribution of sialic acids within the endothelial glycocalyx to the structural and functional permeability properties of the same microvessel in vivo. Single perfused rat mesenteric microvessels were perfused with fluorescent endothelial cell membrane and glycocalyx labels, and imaged with confocal microscopy. A broad range of glycocalyx depth measurements (0.17–3.02μm) were obtained with different labels, imaging techniques and analysis methods. The distance between peak cell membrane and peak glycocalyx label provided the most reliable measure of endothelial glycocalyx anatomy, correlating with paired, numerically smaller values of endothelial glycocalyx depth (0.078±0.016μm) from electron micrographs of the same portion of the same vessel. Disruption of sialic acid residues within the endothelial glycocalyx using neuraminidase perfusion decreased endothelial glycocalyx depth and increased apparent solute permeability to albumin in the same vessels in a timedependent manner, with changes in all three true vessel wall permeability coefficients (hydraulic conductivity, reflection coefficient, and diffusive solute permeability). These novel technologies expand the range of techniques that permit direct studies of the structure of the endothelial glycocalyx and dependent microvascular functions in vivo, and demonstrate that sialic acid residues within the endothelial glycocalyx are critical regulators of microvascular permeability to both water and albumin.